Properties of ultra high performance concrete - Nur Syafiqah Ayub. (2011)
Ultra High Performance Concrete (UHPC) is one of the latest developments in concrete technology. It is commonly defined as a concrete material which has a dense, refined microstructure with improved mechanical performance i.e. an exceptionally high compressive strength of more than 150 MPa and high durability. Numerous research works are currently being done globally concerning the types of UHPC materials used.This research was designed to examine the factors affecting the mechanical properties of UHPC. The factors addressed were the effect of replacing cement with supplementary cementing materials i.e. silica fume and ultrafine slag. Four mechanical properties (compressive strength, flexural properties, tensile splitting strength and modulus of elasticity) were studied. Compressive strength was dependent on the type of supplementary cementing materials used.